2005
DOI: 10.1021/jf051509m
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Engineering of Plant Cells for Biotransformation of Hesperedin into Neohesperidin, a Substrate for Production of the Low-Calorie Sweetener and Flavor Enhancer NHDC

Abstract: Neohesperidin dihydrochalcone (NHDC) is a seminatural, safe, low-calorie sweetener, bitterness blocker, and flavor enhancer with unique properties and applications for the food, beverage, pharmaceutical, and animal feed industries. Current production is limited by the availability of the substrate neohesperidin, a flavonoid that accumulates to significant levels only in the inedible bitter citrus species. We propose a process to convert hesperidin, a tasteless flavonoid extracted from orange peels that are abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 18 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…From that point of view, the CitEST Project is a great source of information concerning gene expression patterns of flavedo as a support to gene expression analysis during fruit development and ripening. Moreover, even though the juice is undoubtedly the most important orange product, growing attention has been paid to citrus flavedoderived compounds such as flavonoids (Frydman et al, 2005) and essential oils (Sawamura et al, 2004;Souza et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…From that point of view, the CitEST Project is a great source of information concerning gene expression patterns of flavedo as a support to gene expression analysis during fruit development and ripening. Moreover, even though the juice is undoubtedly the most important orange product, growing attention has been paid to citrus flavedoderived compounds such as flavonoids (Frydman et al, 2005) and essential oils (Sawamura et al, 2004;Souza et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…B, an increase in the ethanol/water ratio from 40 to 70% coupled with a decrease in the alkaline amount from 200 mg to 0 mg has positive influence on response variable Y . Mauro et al and Frydman et al have revealed that, with hot water extraction, peel/Ca(OH) 2 g/g of 20 and water/peel g/g of 5 were the best conditions for hesperidin extraction from Chenpi, which was presumably related to the environment pH during the hesperidin crystallization. However, exorbitance amount of alkaline may facilitate the release of pectin against antioxidative compounds, which poses a negative influence on the antioxidants extracted from Chenpi.…”
Section: Resultsmentioning
confidence: 99%
“…As seen from the previous examples, the polyphenolic compounds are the most important and abundant types of antioxidants in tree bark. Potential polyphenol uses are broad and include the production of natural food preservatives (Seeram -Heber 2007, Coté et al 2011, Gyawali -Ibrahim 2014, Kobus-Cisowska et al 2014, healthcare, and healthcare-related products (Packer et al 1999, Dzialo et al 2016, Watson et al 2018, natural growth bioregulators (Popa et al 2002, Vyvyan 2002, food and beverage products (Frydman et al 2005, Sawalha et al 2009, and silver nanoparticle production (Fahimirida et al 2019, Ranoszek-Soliwoda et al 2019, Rolim et al 2019. A recent global survey predicted a boom in the polyphenol market due to increasing demand and market size.…”
Section: Introductionmentioning
confidence: 99%